2018
DOI: 10.2196/10120
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of Cognitive Behavioral Therapy Apps for Depression: An Analysis of App Functionality and User Reviews

Abstract: BackgroundHundreds of mental health apps are available to the general public. With increasing pressures on health care systems, they offer a potential way for people to support their mental health and well-being. However, although many are highly rated by users, few are evidence-based. Equally, our understanding of what makes apps engaging and valuable to users is limited.ObjectiveThe aim of this paper was to analyze functionality and user opinions of mobile apps purporting to support cognitive behavioral ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
165
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 53 publications
15
165
2
3
Order By: Relevance
“…Identifying Potentially Relevant Apps and Extensions. Following similar reviews [166,179], we then manually screened the titles and short descriptions (if available; otherwise the first paragraphs of the full description). We included apps and extensions explicitly designed to help people self-regulate their digital device use, while excluding tools intended for general productivity, self-regulation in other domains than digital device use, or which were not available in English (for detailed exclusion criteria, see osf.io/zyj4h).…”
Section: Methodsmentioning
confidence: 99%
“…Identifying Potentially Relevant Apps and Extensions. Following similar reviews [166,179], we then manually screened the titles and short descriptions (if available; otherwise the first paragraphs of the full description). We included apps and extensions explicitly designed to help people self-regulate their digital device use, while excluding tools intended for general productivity, self-regulation in other domains than digital device use, or which were not available in English (for detailed exclusion criteria, see osf.io/zyj4h).…”
Section: Methodsmentioning
confidence: 99%
“…However, only a handful of studies have analyzed mHealth app reviews. These investigations have tended to assess app content quality for specific disorders [ 35 ], app functionality and user experience of a specific intervention [ 36 ], or apps targeting medication adherence [ 37 ]. Consumer perspectives of apps for bipolar disorder [ 35 ] found mostly positive feedback but also a large number of requests for desired functions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, users often did not consider the evidence base or clinical effectiveness of the app. User experience of cognitive behavioral therapy apps for depression [ 36 ] found that users valued the app in supporting their mental well-being and used the app as an adjunct to treatment. Concerns were also highlighted, particularly surrounding the importance of privacy, security, and trust.…”
Section: Introductionmentioning
confidence: 99%
“…Following similar reviews, we coded functionality based on the descriptions, screenshots, and videos available on a tool's store page [cf. 166,[177][178][179]. We iteratively developed a coding sheet of feature categories [cf.…”
Section: Methodsmentioning
confidence: 99%